2006
DOI: 10.1038/sj.bjp.0706507
|View full text |Cite
|
Sign up to set email alerts
|

Study of the mechanisms involved in the vasorelaxation induced by (−)‐epigallocatechin‐3‐gallate in rat aorta

Abstract: 1 This study investigated several mechanisms involved in the vasorelaxant effects of (À)-epigallocatechin-3-gallate (EGCG). 2 EGCG (1 mM-1 mM) concentration dependently relaxed, after a transient increase in tension, contractions induced by noradrenaline (NA, 1 mM), high extracellular KCl (60 mM), or phorbol 12-myristate 13-acetate (PMA, 1 mM) in intact rat aortic rings. In a Ca 2 þ -free solution, EGCG (1 mM-1 mM) relaxed 1 mM PMA-induced contractions, without previous transient contraction. However, EGCG (1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 53 publications
4
50
0
Order By: Relevance
“…The data were examined by one-way analysis of variance (ANOVA) followed by a Tukey-Kramer test for multiple comparisons, and differences were considered significant at an ␣ value of 0.05. The concentration of drugs that caused a 50% inhibition of the response (IC 50 ) was estimated by nonlinear regression analysis (GraphPad Prism software; GraphPad, San Diego, CA, USA) from the concentration-response curves obtained in each case (34).…”
Section: Preparation Of Cell Crude Extracts (Ces) T Vaginalis Trophmentioning
confidence: 99%
“…The data were examined by one-way analysis of variance (ANOVA) followed by a Tukey-Kramer test for multiple comparisons, and differences were considered significant at an ␣ value of 0.05. The concentration of drugs that caused a 50% inhibition of the response (IC 50 ) was estimated by nonlinear regression analysis (GraphPad Prism software; GraphPad, San Diego, CA, USA) from the concentration-response curves obtained in each case (34).…”
Section: Preparation Of Cell Crude Extracts (Ces) T Vaginalis Trophmentioning
confidence: 99%
“…In vascular system, EGCG showed seemingly contradictory actions on vascular tissues, such as a vasorelaxant activity (Chen et al, 2000;Alvarez et al, 2006) and a contractile behavior (Alvarez-Castro et al, 2004), that could be completely opposite reaction. And in small intestine, EGCG inhibits the motility of smooth muscle cells where a cGMP-dependent mechanism may partly be involved (Huang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of EGCG seems to be mediated by an increase of cytosolic cAMP and cGMP concentrations: This is via inhibition of various cyclic nucleotide phosphodiesterase (PDE) isoforms (Alvarez et al, 2006). Also, many authors suggested that cGMP plays important roles in mouse intestinal ICC.…”
Section: Discussionmentioning
confidence: 99%
“…EGCG modulates key regulators of mitochondrial metabolism such as Sirt1 activity [142] and cAMP levels [143,144] in addition to being a specific and safe inhibitor of the Hsa21 gene DYRK1A, a kinase protein involved in brain development and in the control of synaptic plasticity [145]. This makes EGCG an interesting candidate drug for the treatment of DS phenotype.…”
Section: Epigallocatechin-3-gallate (Egcg)mentioning
confidence: 99%